Inscription of Beauty in Female's Body and Restriction of Self in Item Dances of Nepali Movies - Bista, Asmita (JODEM: Journal of Language and Literature, 2023)
In Nepali movies, the female characters construct the image of sensual seductresses who assiduously try to entrap the males through their captivating dance moves. These women appear as enchantresses because they are regulated by the social norms that constrain them to the role of an entertainer. Not only that, since these female characters are bound to entertain the males and to satisfy their carnal desire by offering their body, they put their effort to meet the so-called beauty standard designed by the society. In this ambience, this paper critically examines the reason for creating the image of female’s beauty in the item dances of Nepali films. Equally, the paper analyzes the process of creating an image of the female as a beautiful object. To address these objectives, the concept of ‘disciplining the body’ of Judith Butler, Judith Lorber and Susan Bordo has been used. These critics view that beauty is inscribed on the body through cultural norms. Bordo discusses about the role played by the socializing agencies in disciplining the people’s gender identity as she examines that the body becomes its gender through a series of acts, which are renewed, revised and consolidated through time. In Butler’s perception, social norms bind the individual to acceptable standards of behavior. The paper concludes that since the female performers of these item dances are regulated by the system of beauty that is designed to privilege the male’s desire, they exhibit their body as a beautiful product to the males.